Early dysregulation of cardiac-specific microRNA-208a is linked to maladaptive cardiac remodelling in diabetic myocardium - Shruti Rawal; Prashanth Thevakar Nagesh; Sean Coffey; Isabelle van Hout; Ivor F. Galvin; Richard W. Bunton; Philip J. Davis; Michael Williams; Rajesh Katare (2019)
The diabetic heart undergoes remodelling contributing to an increased incidence of heart failure in individuals with diabetes at a later stage. The molecular regulators that drive this process in the diabetic heart are still unknown. Real-time (RT) PCR analysis was performed to determine the expression of cardiac specific microRNA-208a in right atrial appendage (RAA) and left ventricular (LV) biopsy tissues collected from diabetic and non-diabetic patients undergoing coronary artery bypass graft surgery. To determine the time-dependent changes, cardiac tissue were collected from type 2 diabetic mice at different age groups. A western blotting analysis was conducted to determine the expression of contractile proteins α- and β-myosin heavy chain (MHC) and thyroid hormone receptor-α (TR-α), the negative regulator of β-MHC. To determine the beneficial effects of therapeutic modulation of miR-208a, high glucose treated adult mouse HL-1 cardiomyocytes were transfected with anti-miR-208a. RT-PCR analysis showed marked upregulation of miR-208a from early stages of diabetes in type 2 diabetic mouse heart, which was associated with a marked increase in the expression of pro-hypertrophic β-MHC and downregulation of TR-α. Interestingly, upregulation of miR-208a preceded the switch of α-/β-MHC isoforms and the development of diastolic and systolic dysfunction. We also observed significant upregulation of miR-208a and modulation of miR-208a associated proteins in the type 2 human diabetic heart. Therapeutic inhibition of miR-208a activity in high glucose treated HL-1 cardiomyocytes prevented the activation of β-MHC and hence the hypertrophic response. Our results provide the first evidence that early modulation of miR-208a in the diabetic heart induces alterations in the downstream signaling pathway leading to cardiac remodelling and that therapeutic inhibition of miR-208a may be beneficial in preventing diabetes-induced adverse remodelling of the heart.